BaseballB6236
New member
- Joined
- Sep 20, 2010
- Messages
- 9
Find the partial fraction decomposition of
-3
---------------
4x^2-6x+2
so far I have:
-3 -3
---------------- = ----------------------
2(2x^2-3x+1) 2(2x-1)(x-1)
= A/2 + B/ 2x-1 + C/x-1
= A(2x-1)(x-1) B(2)(x-1) C(2)(2x-1)
------------------------- + ---------------------- + --------------------
2(2x-1)(x-1) 2(2x-1)(x-1) 2(2x-1)(x-1)
on the right track? what should I do next..thanks in advance
-3
---------------
4x^2-6x+2
so far I have:
-3 -3
---------------- = ----------------------
2(2x^2-3x+1) 2(2x-1)(x-1)
= A/2 + B/ 2x-1 + C/x-1
= A(2x-1)(x-1) B(2)(x-1) C(2)(2x-1)
------------------------- + ---------------------- + --------------------
2(2x-1)(x-1) 2(2x-1)(x-1) 2(2x-1)(x-1)
on the right track? what should I do next..thanks in advance